2022
DOI: 10.33487/edumaspul.v6i2.3874
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of ‘Independent Campus-Freedom to Learn’ Policy

Abstract: The policy of ‘Independent Campus-Freedom to Learn’ known as MBKM is currently participated by the students in Indonesia as it could provide the credit transfer of 20-60. This research aimed to investigate the students’ perceptions on the implementation of MBKM. The participants of this research were 98 students of Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta. The method used was a descriptive analysis design. The instrument used was a questionnaire completed by the students who already joined MBKM progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
2
1
0
Order By: Relevance
“…This finding is in line with the results of previous research which stated that 67.5% of students were interested in the MBKM program organized by the Directorate General of Higher Education, Research, and Technology (Laga et al, 2022;Setiana et al, 2022). It is also supported by another study which stated that 81% of the students were eager to take MBKM program in the next semester (Apoko et al, 2022;Kamalia & Andriansyah, 2021). It means that MBKM programs offers many benefits for students.…”
Section: Students' Participation To Mbkm Policysupporting
confidence: 90%
“…This finding is in line with the results of previous research which stated that 67.5% of students were interested in the MBKM program organized by the Directorate General of Higher Education, Research, and Technology (Laga et al, 2022;Setiana et al, 2022). It is also supported by another study which stated that 81% of the students were eager to take MBKM program in the next semester (Apoko et al, 2022;Kamalia & Andriansyah, 2021). It means that MBKM programs offers many benefits for students.…”
Section: Students' Participation To Mbkm Policysupporting
confidence: 90%
“…The current study aimed to examine the students' awareness on the ILIC in the study program of Mathematics education. The result of this study is closely related to a study by Apoko, Handayani, Hanif, & Hendriana (2023) which positively showed that the level of knowledge of students who participated in the emancipated learning program was very high (92%) and with great enthusiasm (Apoko, Hendriana, Umam, & Handayani, 2022). This indicated that universities were prepared with ILIC-oriented curricula, where curriculum development was carried out in accordance with field needs (Sopiansyah et al, 2022) so that there was a change in the concept of higher education for the better so.…”
Section: The Impact To Ilicsupporting
confidence: 72%
“…In response to these issues, Nadiem Makarim, the Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia, launched the Merdeka Belajar Kampus Merdeka or Emancipated learning-Independent Campus in 2020, hereinafter called MBKM. This optional program allows students both in state and private universities to study outside of their main study program and campus (Apoko et al, 2022).…”
Section: Introductionmentioning
confidence: 99%